FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PETANI DALAM PEMANFAATAN LIMBAH TONGKOL JAGUNG (Zea mays L) MENJADI BRIKET DI KECAMATAN SEI BINGAI KABUPATEN LANGKAT - Rizaldi, Restu Bima; Harahap, Nurliana; Sasvita, Wikka (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
The purpose of this study was to determine the level of interest and influencing factors in utilizing corncob waste into briquettes. This study was conducted from March to May 2025. The data collection method was a combination method consisting of observation, questionnaires, interviews, and documentation. The data analysis method used a Likert scale and multiple linear regression. The results of the study showed that the level of farmer interest in utilizing corncob waste into briquettes was relatively high with an interest of 70.2%. Simultaneously, the variables of education, technology, experience, capital, income, and marketing influenced farmer interest. Partially, the variables of technology, capital, income, and marketing significantly influenced farmer interest, while the variables of education and experience did not significantly influence farmer interest.